Imagens do Brasil (análise do nacionalismo na adaptação de um romance histórico para a televisão). - Frighetto, Gisele Novaes (2005)
The adaptation from A Muralha, a historical novel written by Dinah Silveira de Queiroz, into a television soap opera, express, among other aspects, the transmission of national myths and symbols into television soap operas as a common practice. A Muralha was broadcasted by Globo Channel during The 500 years Celebration of Brazil Discovery, in 2000, and it had the paulista excursions as the main theme. Besides that, this soap opera recovered national Brazilian character ideologies, similarly to what The 500 years Celebration did. At this time, we could see the celebration of Nation s birth, and, in order to achieve a better understanding about this subject, we studied European nationalism and its consequences in Brazil during 19th and 20th centuries. We analyzed the potential of the historical novels to integrate the nationally imagined communities and we saw how television, Globo Channel specifically, gradually took the part of transmitting Images of Brazil through soap operas, to a wide audience and many times in partnership with the Brazilian State. The exhibition of the soap opera A Muralha happened in this context, from January 4 to March 28 in 2000.